ESTIMASI BIAYA PRODUKTIVITAS YANG HILANG AKIBAT KEMATIAN DINI PASIEN COVID-19 DI RS PKU MUHAMMADIYAH GAMPING - Andriani, Yuni; Sugiyono, Sugiyono (Jurnal Ekonomi Kesehatan Indonesia, 2023)
COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The COVID-19 virus infection has had an impact on the global health and economic system, including in developing countries. This research is an observational study by estimating the indirect costs of lost productivity due to premature deaths in COVID-19 patients at PKU Muhammadiyah Gamping Hospital in 2021 and knowing the characteristics of the patients. This hospital was chosen as the research site because the percentage of Bed Occupancy Rate (BOR) was the highest in Sleman Regency in 2021, reaching 68.94%. The results of the research show that the characteristics of inpatient COVID-19 patients at PKU Muhammadiyah Gamping in 2021 are dominated by those aged over 60 years, 139 (52.26%) patients, with the largest gender being male, namely 146 (55%) patients. Patients had a mean hospitalization value of 7.56 with a median cost of 7 days, a minimum of 1 day, and a maximum of 32 days. The patient's comorbid status was 195 (73.3) patients who were diagnosed with COVID-19 and had comorbid diseases with the highest percentage being diabetes mellitus, 96 (36.1) patients. These results indicate that the cost of lost productivity due to premature death in COVID-19 cases at PKU Muhammadiyah Gamping Hospital for men is higher than for women. This is influenced by the death rate and average income which are predominantly higher in male subjects.